Identifikasi Ikan Hiu Bycatch Di Samudra Hindia Berdasarkan DNA Barcoding Dalam Upaya Konservasi - Yuni Debora Prasicilia Sitorus; Ida Ayu Astarini; I Made Antara (Journal of Marine and Aquatic Sciences, 2023)
The most potential shark fishing area in Indonesia is the Indian Ocean. One of the fishing ports that has bycatch shark is Benoa Harbor. The purpose of this research is to identify species to determine the conservation status of bycatch shark species from body tissue samples caught in the Indian Ocean in conservation efforts. The research was conducted from January to March 2021 at Pangkalan Pengawasan Sumber Daya Kelautan dan Perikanan (PSDKP) of Benoa Harbor. This study uses an exploratory method with survey techniques. The data used in this study are primary data in the form of shark fin samples in the study area and secondary data in the form of locations where sharks are caught by fishermen based on the PSDKP database. The results showed that sharks bycatch from body tissue samples caught in the Indian Ocean based on morphological identification and DNA barcoding techniques were Prionace glauca, Isurus paucus, Sphyrna zygaena, Isurus oxyrinchus, Alopias superciliosus and Carcharhinus longimanus. Bycatch sharks from body tissue samples caught in the Indian Ocean based on morphological identification and DNA barcoding techniques have close phylogenetic relationships with the Carcharhinidae, Sphyrnidae, Alopiidae and Lamnidae families. Bycatched shark from body tissue samples caught in the Indian Ocean based on morphological identification and DNA barcoding techniques has a conservation status, near threatened for Prionace glauca species, vulnerable for Sphyrna zygaena species and Alopias superciliosus species, endangered for Isurus paucus species and Isurus oxyrinchus species, critically endangered for Carcharhinus longimanus species.